Perkembangan Kritik Sastra Arab Masa Abbasiyah - Hedrilana, Yoga (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2024)
It is evident that literary criticism advanced significantly throughout the Abbasid era based on the government's achievements. During the Abbasid era, science advanced significantly. The objectives of this study are to describe the elements that promoted the growth of literary criticism, pinpoint patterns in literary criticism throughout the Abbasid era, and explain the rise of Manhaji literary critique. Data as gathered using the Research Library as part of the historical research methodology. The findings of the study demonstrate how the Abbasid era's attempts to translate a number of books promoted scientific advancement. This translation procedure allows literary criticism to be evaluated from a ider range of viewpoints than just language and literature. This study also found that the tendency of literary criticism during the Abbasid period as one of the characteristics of the triumph of classical literary criticism.